Effect of Various Agro-Residues on Nutritive Value of Pleurotus eryngii (DC. ex Fr.) Quel. var. ferulae Lanzi - Akyuz, Mehmet; Kirbag, Sevda (Ankara Univ, Fac Agr, 2010)
In this study, the effect of various compost medium on the nutritive value of P. eryngii var. ferulae were determined. Dry matter, moisture, crude ash, protein, fat and organic matter were determined as 91.7-92.7, 7.3-8.3, 5.4-6.1, 8.5-19.7, 2.5-4.1 and 85.8-86.9% of air-dried weight, respectively. There were no significant differences in crude ash and organic matter content for P. eryngii var. ferulae grown on various agro-residues. Crude protein and fat contents varied significantly, the lowest protein content was obtained in natural wild sample (8.5%), whereas the highest were obtained in WS + 10% RB (18.0%), WS-CS (1:1) + 10% RB (18.5%), WS + 20% RB (18.9%) and WS-CS (1:1) + 20% RB (19.7%). Minimum crude fat content was 2.5% in WS-CS (1:1), maximum was 3.9-4.1% in WS + 10% RB, WS + 20% RB, WS-CS (1:1) + 10% RB and WS-CS (1:1) + 20% RB. Mineral contents varied significantly, their contents were determined to be 14.3-22.6 for K, 0.12-0.70 for Ca and 0.1-0.3 for mg g(-1) Na as macro elements, 519.5-1142.3 for Fe, 33.5-102.5 for Zn, 41.6-64.6 for Mn, 25.8-48.5 for Cu and 1.3-2.3 for mg kg(-1) Cr as micro elements. Pb, Co, Ni and Cd concentrations were under the detection limit of the metod used.
De?işik tarımsal artıkların Pleurotus eryngii (DC. ex Fr.) quel. var. ferulae Lanzi'nin besin de?erleri üzerine etkisi
Keywords: Agro-residues; Crude fat; Crude protein; Element; P. eryngii var. ferulae